Gold in the service of the developing countries : a financing plan - Angelopoulos, Angelos Theodōrou (Geneva : Nagel Publishers, 1969)
This book contains the author radical plan for the financing of assistance to the developing countries. This plan was submitted in November 1968 to Mr. Robert S. McNamara, President of the World Bank.
Includes bibliographical references.
usc 7/9/2017
Loans
Keywords: Finance; Gold; Developing countries